2020
DOI: 10.1111/ene.14391
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rituximab in myasthenia gravis: a French multicentre real‐life study

Abstract: Background and purpose: Fifteen percent of patients with myasthenia gravis (MG) are refractory to conventional treatment. Case reports and a few studies show probable benefit of rituximab in these cases. Our objective was to assess the efficacy and the safety of rituximab in patients with MG, in a multicentric real-life study. Method: Inclusion criteria were: age > 18 years; MG with anti-acetylcholine receptor (AChR) antibodies, anti-muscle-specific kinase (MuSk) antibodies or significant decrement after repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 32 publications
0
48
1
Order By: Relevance
“…The only controlled study of rituximab in MG (BeatMG) reported negative results for the primary study outcome, so far only by abstract 7 . In contrast, several open studies have reported positive results in up to 80% of the patients, 8,9 similar to Zhang et al 1 Retention rates for rituximab in MG have not been communicated until this new Chinese study. However, in MS, rituximab is clearly superior to all other examined treatments regarding maintenance over time.…”
mentioning
confidence: 72%
“…The only controlled study of rituximab in MG (BeatMG) reported negative results for the primary study outcome, so far only by abstract 7 . In contrast, several open studies have reported positive results in up to 80% of the patients, 8,9 similar to Zhang et al 1 Retention rates for rituximab in MG have not been communicated until this new Chinese study. However, in MS, rituximab is clearly superior to all other examined treatments regarding maintenance over time.…”
mentioning
confidence: 72%
“…These studies made formal or informal comparisons from before treatment to after treatment and described outcomes in cohorts of patients who all received rituximab. Three studies 18,23,26 were multi-centre, and 6 studies [19][20][21][22]24,25 were conducted at a single centre.…”
Section: Methodsmentioning
confidence: 99%
“…The non-randomized studies were conducted in Austria, 26 China, 21,24 France, 18 India, 25 Italy, 20 the Republic of Korea, 23 and the US. 19,22…”
Section: Country Of Originmentioning
confidence: 99%
“…Rituximab is commonly used in refractory cases of myasthenia gravis (MG) in which conventional immunomodulatory therapies have failed, even though evidence suggests that rituximab performs better in new-onset generalized MG than in cases that have become refractory to conventional immunosuppressants [89]. Uncontrolled studies have provided evidence of efficacy in several measures of efficacy such as clinical improvement, time to relapse, reduction in steroid use [90], decrease in antibody titers [91] and reduced inhospital costs in a proportion of MG patients [92][93][94][95][96][97]. The efficacy of rituximab may be more pronounced in anti-Musk Ab MG, in which clinical improvement is associated with significant reduction in anti-Musk Ab titers, even to levels below detection [94,95,97,98].…”
Section: Myasthenia Gravis (Mg)mentioning
confidence: 99%